Cryo‐EM structure of the ribosome functional complex of the human pathogen Staphylococcus aureus at 3.2 Å resolution. Issue 21 (10th September 2020) - Golubev, Alexander; Fatkhullin, Bulat; Khusainov, Iskander; Jenner, Lasse; Gabdulkhakov, Azat; Validov, Shamil; Yusupova, Gulnara; Yusupov, Marat; Usachev, Konstantin
Abstract : Staphylococcus aureus is a bacterial pathogen and one of the leading causes of healthcare‐acquired infections in the world. The growing antibiotic resistance of S. aureus obliges us to search for new drugs and treatments. As the majority of antibiotics target the ribosome, knowledge of its detailed structure is crucial for drug development. Here, we report the cryo‐EM reconstruction at 3.2 Å resolution of the S. aureus ribosome with P‐site tRNA, messenger RNA, and 10 RNA modification sites previously not assigned or visualized. The resulting model is the most precise and complete high‐resolution structure to date of the S. aureus 70S ribosome with functional ligands. Abstract :